A curriculum-based laboratory kit for flexible teaching and learning of practical chemistry - Hee Ting, Wong; Siong Fong, Sim (Walter de Gruyter, 2022)
Laboratory practical is an essential component for effective learning of science. To provide laboratory experience can be a challenge to some rural schools with limited laboratory facilities. The situation was exacerbated when schools were close due to the COVID pandemic. This paper reports a laboratory kit designed based on the Standard Curriculum for Secondary Schools in Malaysia (KSSM). The kit was evaluated by students and experienced teachers from town and rural schools. Pre- and post-test was conducted with the students before and after using the kit. A questionnaire was disseminated to appraise the students’ perceptions on practical learning. There was a significant improvement (p < 0.05) in the overall score of the post-test comparing to the pre-test. Both rural and town schools demonstrated a marked increase in the overall mean scores in the post-test. There was also improvement in affection for chemistry among students after using the kit. The practical kit can be deployed in schools with laboratory constraints and to be used outside the school settings. It was designed to be affordable, safe and environmental-friendly, providing individualized hands-on exposure.